Local-Government-Owned Commercial Banks’ Performance Influencer Factors in Indonesia - Christina Liem; Yunita Ismail Masjud; Alexander William Candra (President University, 2017)
AbstractAs one of government-owned banks; local-government-owned commercial banks in Indonesia have unique and critical roles to support local government to develop stronger local economic conditions. Moreover, study about influencer factors of local-government-owned commercial banks’ performance become important and urgently needed, since only few studies about this previously. Meanwhile, commercial bank’s performance is influenced by internal influencers and external influencers. Therefore, this study focuses on bank’s soundness as internal factor influencer; and selected macroeconomics indicators as external factors influencer toward bank’s performance. The result of this study shows even though CAR; CIR; NIM of all 19 local-government-owned commercial banks in Indonesia have reached first rank of the banks’ soundness measurement; however, only 1 bank has reached first rank in LDR; and only 2 banks have reached first rank in NPL. Therefore, this study shows that local-government-owned commercial banks in Indonesia have serious problem in liquidity and asset quality. On the other hand, this study proves that local GDP growth rate and local GINI ratio - as external influencer – have no significant influencing toward banks’ performance. Finally, this study concludes those local-government-owned commercial banks’ performances - that represented by ROAA and ROAE - have been influenced by banks’ soundness significantly; and there are no significant influencers from external factors. Thus, this study suggests the local-government-owned commercial banks to focus to increase and maintain their banks’ soundness in order to increase their performance. Keywords: CAMEL; Banks’ Soundness; Macroeconomics; Banks’ Performance; Commercial Banks